LISTENING COMPREHENSION STRATEGIES APPLIED BY ENGLISH LANGUAGE LEARNERS - Sitti Hadijah; Shalawati Shalawati (ELT-Lectura, 2018)
This paper depicts a part of a research project, focused on exploring three listening comprehension strategies applied by the English learners in interpretative listening subject; (a) meta-cognitive strategies consist of directed attention, selective attention, planning, monitoring, and evaluation; (b) cognitive strategies include listening for gist and detail, inference, prediction, visualization, summarizing, and note-taking; (c) Social/affective strategies, such as cooperation. Hence, mixed-method research was employed to describe what listening comprehension strategies used more often by English Students at Universitas Islam Riau. Thirty-seven fresh year learners taking interpretative listening subject were encouraged to participate in this research by filling out questionnaire adopted form Cross (2009). The data collected will both qualitatively and quantitatively analyzed. Thirty-two statements included in the questionnaire were categorized intro three groups; cognitive (15), meta-cognitive (15), and socio-affective (2). The finding reveals that the learners had been familiar will the strategies and frequently apply them based on their needs in listening processes, such as before, while, and after listening.